1983
DOI: 10.1111/j.1471-4159.1983.tb13668.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine and Choline in Neuronal Tissue Measured by HPLC with Electrochemical Detection

Abstract: A simple, rapid method is presented for the determination of acetylcholine (ACh) and choline (Ch) in neuronal tissue using HPLC with electrochemical detection. The method is based on the separation of ACh and Ch by reverse-phase HPLC and mixing the effluent as it emerges from the column with acetylcholinesterase and Ch oxidase, which converts endogenous Ch and Ch produced by the hydrolysis of ACh to betaine and hydrogen peroxide. Production of hydrogen peroxide is continuously monitored electrochemically. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(137 citation statements)
references
References 8 publications
(8 reference statements)
1
136
0
Order By: Relevance
“…Background signal was determined by assaying citrate-phosphate buffer instead of cell extract. Acetylcholine (ACh) levels were determined by HPLC-ED with an enzymatic reactor containing acetylcholinesterase and choline oxidase based on the method of Potter et al (1983). The materials used were obtained from Bioanalytical Systems Inc. (West Lafayette, IN).…”
Section: Radioligand Binding Studiesmentioning
confidence: 99%
“…Background signal was determined by assaying citrate-phosphate buffer instead of cell extract. Acetylcholine (ACh) levels were determined by HPLC-ED with an enzymatic reactor containing acetylcholinesterase and choline oxidase based on the method of Potter et al (1983). The materials used were obtained from Bioanalytical Systems Inc. (West Lafayette, IN).…”
Section: Radioligand Binding Studiesmentioning
confidence: 99%
“…This assay is based on the separation of acetyl Ch and Ch by reverse-phase HPLC (Potter et al 1983). For the electrolytic cell, the dual platinum action electrode and Ag/AgC12 electrode were used as a comparative electrode.…”
Section: Measurement Of Schmentioning
confidence: 99%
“…Recent observations, however, have indicated that the mechanism of endogenous ACh release from brain slices is different from that of preloaded [3H]ACh (23). Since recent advancements in HPLC procedures using electrochemical detection (13,14) have made possible the simultaneous measurements of ACh and choline with reasonable sensitivity, we have used these procedures with a continuous tissue transfer system to minimize enzymatic degradation of released endogenous ACh by AChE. In vitro addition of denbufylline (10-4 M) significantly enhanced 20 mM KC1 (a submaximal dose for ACh release)-evoked endogenous ACh release from striatal slices under these experimental conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For the measurements of ACh, ACh was extracted from the tissue samples according to the method of Potter et al (13) and Igarashi et al (14). The samples were then weighed before the homogenization in 2 ml of a 1 N formic acid : acetone (15:85) mixture and then centrifuged at 1,700 X g for 20 min at 4°C.…”
Section: Measurement Of Ach and Camp Contentsmentioning
confidence: 99%
See 1 more Smart Citation